Rifampin resistance and its fitness cost in Riemerella anatipestifer - Sun, Jiakai (BMC Microbiol, 2019)
BACKGROUND: Riemerella anatipestifer (R. anatipestifer) is one of the most important poultry pathogens worldwide, with associated infections causing significant economic losses. Rifampin Resistance is an important mechanism of drug resistance. However, there is no information about rpoB mutations conferring rifampin resistance and its fitness cost in Riemerella anatipestifer. RESULTS: Comparative analysis of 18 R.anatipestifer rpoB sequences and the determination of rifampin minimum inhibitory concentrations showed that five point mutations, V382I, H491N, G502K, R494K and S539Y, were related to rifampin resistance. Five overexpression strains were constructed using site-directed mutagenesis to validate these sites. To investigate the origin and fitness costs of the rpoB mutations, 15 types of rpoB mutations were isolated from R. anatipestifer ATCC 11845 by using spontaneous mutation in which R494K was identical to the type of mutation detected in the isolates. The mutation frequency of the rpoB gene was calculated to be 10(− 8). A total of 98.8% (247/250) of the obtained mutants were located in cluster I of the rifampin resistance-determining region of the rpoB gene. With the exception of D481Y, I537N and S539F, the rifampin minimum inhibitory concentrations of the remaining mutants were at least 64 μg/mL. The growth performance and competitive experiments of the mutant strains in vitro showed that H491D and 485::TAA exhibit growth delay and severely impaired fitness. Finally, the colonization abilities and sensitivities of the R494K and H491D mutants were investigated. The sensitivity of the two mutants to hydrogen peroxide (H(2)O(2)) and sodium nitroprusside (SNP) increased compared to the parental strain. The number of live colonies colonized by the two mutants in the duckling brain and trachea were lower than that of the parental strain within 24 h. CONCLUSIONS: Mutations of rpoB gene in R. anatipestifer mediate rifampin resistance and result in fitness costs. And different single mutations confer different levels of fitness costs. Our study provides, to our knowledge, the first estimates of the fitness cost associated with the R. anatipestifer rifampin resistance in vitro and in vivo. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12866-019-1478-7) contains supplementary material, which is available to authorized users.